Employability skills framework for engineering graduate in Malaysia - Zaharim A.; Yusoff Y.M.D.; Omar M.Z.; Basri H. (2023)
The purpose of this paper is to propose an engineering employability skill framework that will allow the concept to be explained easily and that can be used as a framework for working with engineering graduates to develop their employability before entering workforce. The framework was developed from existing researches on engineering employability skill issues and the requirement of the accreditation of engineering programme. The various criteria of employability skills related to engineering included in the framework are discussed and their criteria justified bases on literature review of existing studies. The framework sets out exactly what is meant by engineering employability, in clear and simple terms, and the framework suggests directions for interaction between the various criteria that being identified. The framework can be used to explain the concept of employability to those new to the subject, and particularly to engineering students and their future employer. It will be a useful tool for lecturers, careers advisors, employers and any other practitioners involved in employability skills. It will also be used to develop a model and a measurement tool for engineering employability skill. This paper contributes insights into the linking of graduate attributes, using national accreditation criteria and the framework of engineering employability skills from locally and globally expectation.